Peculiarities of Acquisition of Inheritance by Actual Possession in Georgian Law and Legislative Guarantees for the Protection of the Legal Heir - Leonidze, Irakli (Alternative Dispute Resolution Yearbook, 2020)
Annotation is available in Georgian